2011
DOI: 10.1071/he11406
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion interventions to address climate change using a primary health care approach: a literature review

Abstract: Issue addressed This project explored the literature in which key concepts in primary health care and health promotion are overtly applied to the problem of climate change. This paper contains a discussion of the literature relevant to health promotion principles and intervention strategies for addressing climate change mitigation and adaptation in the primary health care sector. The concept of primary health care is that used by the World Health Organization, based on the Declaration of Alma Ata and often ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Reflecting the tradition of systematic reviews in the health sciences, health-related adaptation was the focus of six articles (Walker et al 2011;Hosking and Campbell-Lendrum 2012;Bouzid et al 2013;Cheng and Berry 2013;Poutiainen et al 2013;Toloo et al 2013). The most dominant adaptation focus within which systematic reviews have penetrated has been reviewing lessons from, and trends in, adaptation governance (Hardee and Mutunga 2010;Berrang-Ford et al 2011;Ford et al 2011;Pearce et al 2011;Ford et al 2012a, b;Larsen et al 2012;Murtinho and Hayes 2012;Biesbroek et al 2013;Kamau and Mwaura 2013;Vink et al 2013).…”
Section: Systematic Review For Adaptation Research: Challenges and Comentioning
confidence: 99%
See 2 more Smart Citations
“…Reflecting the tradition of systematic reviews in the health sciences, health-related adaptation was the focus of six articles (Walker et al 2011;Hosking and Campbell-Lendrum 2012;Bouzid et al 2013;Cheng and Berry 2013;Poutiainen et al 2013;Toloo et al 2013). The most dominant adaptation focus within which systematic reviews have penetrated has been reviewing lessons from, and trends in, adaptation governance (Hardee and Mutunga 2010;Berrang-Ford et al 2011;Ford et al 2011;Pearce et al 2011;Ford et al 2012a, b;Larsen et al 2012;Murtinho and Hayes 2012;Biesbroek et al 2013;Kamau and Mwaura 2013;Vink et al 2013).…”
Section: Systematic Review For Adaptation Research: Challenges and Comentioning
confidence: 99%
“…Consideration of context, processes, and mechanisms of causality may require more time commitment per document than extraction of key estimates or discrete items of information. Many realist or in-depth reviews, for example, are conducted using fewer than 50 articles, often 30-40 documents (Bouzid et al 2013;Cheng and Berry 2013;Kajan and Saarinen 2013;Linnenluecke et al 2013), and even in-depth qualitative systematic analyses with as few as 15-20 articles (Walker et al 2011;Toloo et al 2013). Research has shown that systematic review of complex and heterogeneous literature bases cannot rely solely on strict keyword searches (Greenhalgh and Peacock 2005), and this is likely to apply to many complex adaptation policy and practice questions.…”
Section: Literature and Information Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few authors have begun to envision the changes that the health care system will need to undertake in response to climate change (Blashki et al, 2007; Ebi, 2011; Parker, 2011; Podein and Hernke, 2010; Richardson et al, 2009; Rosenblatt, 2005; Walker et al, 2011). Several of these have to do with infrastructure and technology.…”
mentioning
confidence: 99%
“…11 However, literature on climate change and health promotion practice remains incomplete, with research gaps in this area clearly evident. 12 It is imperative that Australia's future efforts to mitigate and adapt to climate change continue, with priority given to investment in programs and policies to address food insecurity and increase access to healthy foods for all vulnerable populations.…”
mentioning
confidence: 99%